2000
DOI: 10.1016/s0895-7061(99)00265-4
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise training fails to reduce blood pressure in nondipper-type hypertension

Abstract: To assess whether aerobic exercise training is an effective and an alternative method to control blood pressure (BP) in hypertension, 32 uncomplicated, never treated patients suffering from mild-to-moderate essential arterial hypertension (EAH) were included in an aerobic exercise training program using a regular standardized cycle ergometer exercise for 3 months. In all EAH patients, before and after the exercise training period, ambulatory BP monitoring (ABPM) was performed and several metabolic variables we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
3
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 28 publications
1
23
3
6
Order By: Relevance
“…Not only were Non-Dippers found to respond to exercise treatment, but also Non-Dippers reduced their nighttime systolic blood pressure (À10.17 2.70 mmHg) despite the TOD for exercise. The reduction in systolic blood pressure in Non-Dippers contradicts the findings of Nami and collegues, 12 who reported aerobic exercise training failed to reduce blood pressure in nondipping hypertension.…”
Section: Ambulatory Blood Pressure Monitoringcontrasting
confidence: 58%
See 4 more Smart Citations
“…Not only were Non-Dippers found to respond to exercise treatment, but also Non-Dippers reduced their nighttime systolic blood pressure (À10.17 2.70 mmHg) despite the TOD for exercise. The reduction in systolic blood pressure in Non-Dippers contradicts the findings of Nami and collegues, 12 who reported aerobic exercise training failed to reduce blood pressure in nondipping hypertension.…”
Section: Ambulatory Blood Pressure Monitoringcontrasting
confidence: 58%
“…The additional important findings in this study include: (1) Non-Dippers respond to exercise treatment, (ie both morning and evening exercise produced a reduction in nighttime systolic blood pressure in Non-Dippers) and (2) the duration of the blood pressure reduction appears to be greater than 12 h. Table 6 summarizes these findings in relationship to the literature. Non-Dippers were investigated in the study because (1) they have been identified as nonresponders to exercise 12 and (2) non-dipping hypertension is associated with more serious end-organ damage and higher incidence of cardiovascular complications than Dippers. 11 A single bout of exercise was chosen for this study because it may be the initial step to investigate the effectiveness of exercise on blood pressure reduction in populations previously identified as nonresponders.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations